2017
DOI: 10.1021/acs.jpclett.6b02881
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Energy Transfer by Coherent and Incoherent Mechanisms in the Peridinin–Chlorophyll a Protein

Abstract: Excitation energy transfer from peridinin to chlorophyll (Chl) a is unusually efficient in the peridinin-chlorophyll a protein (PCP) from dinoflagellates. This enhanced performance is derived from the long intrinsic lifetime of 4.4 ps for the S (1B) state of peridinin in PCP, which arises from the electron-withdrawing properties of its carbonyl substituent. Results from heterodyne transient grating spectroscopy indicate that S serves as the donor for two channels of energy transfer: a 30 fs process involving q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 51 publications
4
45
0
Order By: Relevance
“…To check for the presence of electronic coherences between Per and Chl states, whose relevance has been recently suggested in the literature 24 , 25 , the beating behavior of the rephasing signal (recorded with laser 3) in the S 2 /Q y cross-peak region has been carefully scrutinized, applying a recently proposed method based on a time-frequency transform (TFT) analysis 38 , 39 . Given an oscillating trace, this analysis allows extracting not only the main frequency components contributing to the beating, as in conventional Fourier transform, but also their time behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To check for the presence of electronic coherences between Per and Chl states, whose relevance has been recently suggested in the literature 24 , 25 , the beating behavior of the rephasing signal (recorded with laser 3) in the S 2 /Q y cross-peak region has been carefully scrutinized, applying a recently proposed method based on a time-frequency transform (TFT) analysis 38 , 39 . Given an oscillating trace, this analysis allows extracting not only the main frequency components contributing to the beating, as in conventional Fourier transform, but also their time behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Like for other antenna complexes bearing Cars, femtosecond spectroscopic experiments on PCP have also suggested the presence of ultrafast channels of EET from S 2 to the Q bands of Chl 4 , 7 9 , 23 (Q x and/or vibronic states of Q y ), also with possible contributions of coherent pathways 24 , 25 . However, clear and direct evidence is still lacking to identify the main pathways of energy flow from Pers to Chls, and their timescales, including the role of vibrational modes on the dynamics.…”
Section: Introductionmentioning
confidence: 87%
“…Hence, the calculation of these parameters on the BChl of FMO protein is an important subject to study. We also note that the quantum coherence studies of the FMO complex have been reported in a number of works to elucidate the quantum mechanical time-dependent phenomenon associated with the process of photosynthesis [32][33][34][35][36][37][38][39][40][41][42]. Moreover, the mutation of the FMO light harvesting complex can cause changes in the observed phenomenon of quantum coherence.…”
Section: Introductionmentioning
confidence: 80%
“…These results, however, are very sensitive to the employed computational approach, since the lowest excited state of carotenoids is very difficult to assess [ 78 ]. Still, experimental evidence for the theoretically modelled type of mixed EET (with S 2 preference) exists [ 79 ].…”
Section: The Photosynthetic Apparatus Of Plants (And Algae)mentioning
confidence: 99%